Various Enterotoxin and Other Virulence Factor Genes Widespread Among Bacillus cereus and Bacillus thuringiensis Strains - Kim, Min-Ju; Han, Jae-kwang; Park, Jong-Su; Lee, Jin-Sung; Lee, Soon-Ho; Cho, Joon-Il; Kim, Keun-Sung (Journal of microbiology and biotechnology, 2015)
Many strains of Bacillus cereus cause gastrointestinal diseases, and the closely related insect pathogen Bacillus thuringiensis has also been involved in outbreaks of diarrhea. The diarrheal diseases are attributed to enterotoxins. Sixteen reference strains of B. cereus and nine commercial and 12 reference strains of B. thuringiensis were screened by PCR for the presence of 10 enterotoxigenic genes (hblA, hblC, hblD, nheA, nheB, nheC, cytK, bceT, entFM, and entS), one emetogenic gene (ces), seven hemolytic genes (hlyA, hlyII, hlyIII, plcA, cerA, cerB, and cerO), and a pleiotropic transcriptional activator gene (plcR). These genes encode various enterotoxins and other virulence factors thought to play a role in infections of mammals. Amplicons were successfully generated from the strains of B. cereus and B. thuringiensis for each of these sequences, except the ces gene. Intriguingly, the majority of these B. cereus enterotoxin genes and other virulence factor genes appeared to be widespread among B. thuringiensis strains as well as B. cereus strains.